Sclerostin modulates mineralization degree and stiffness profile in the fibrocartilaginous enthesis for mechanical tissue integrity - Yambe, Shinsei; Yoshimoto, Yuki; Ikeda, Kazutaka; Maki, Koichiro; Takimoto, Aki; Tokuyama, Akihide; Higuchi, Shinnosuke; Yu, Xinyi; Uchibe, Kenta; Miura, Shigenori; Watanabe, Hitomi; Sakuma, Tetsushi; et al. (Frontiers in Cell and Developmental Biology, 2024)
Fibrocartilaginous entheses consist of tendons, unmineralized and mineralized fibrocartilage, and subchondral bone, each exhibiting varying stiffness. Here we examined the functional role of sclerostin, expressed in mature mineralized fibrochondrocytes. Following rapid mineralization of unmineralized fibrocartilage and concurrent replacement of epiphyseal hyaline cartilage by bone, unmineralized fibrocartilage reexpanded after a decline in alkaline phosphatase activity at the mineralization front. Sclerostin was co-expressed with osteocalcin at the base of mineralized fibrocartilage adjacent to subchondral bone. In Scx-deficient mice with less mechanical loading due to defects of the Achilles tendon, sclerostin + fibrochondrocyte count significantly decreased in the defective enthesis where chondrocyte maturation was markedly impaired in both fibrocartilage and hyaline cartilage. Loss of the Sost gene, encoding sclerostin, elevated mineral density in mineralized zones of fibrocartilaginous entheses. Atomic force microscopy analysis revealed increased fibrocartilage stiffness. These lines of evidence suggest that sclerostin in mature mineralized fibrochondrocytes acts as a modulator for mechanical tissue integrity of fibrocartilaginous entheses.